2022
DOI: 10.1186/s12879-022-07209-5
|View full text |Cite
|
Sign up to set email alerts
|

A sharp decrease in reported non-COVID-19 notifiable infectious diseases during the first wave of the COVID-19 epidemic in the Rotterdam region, the Netherlands: a descriptive study

Abstract: Background The Public Health Services in the Rotterdam region, the Netherlands, observed a substantial decrease of non-COVID-19 notifiable infectious diseases and institutional outbreaks during the first wave of the COVID-19 epidemic. We describe this change from mid-March to mid-October 2020 by comparing with the pre-COVID-19 situation. Methods All cases of notifiable diseases and institutional outbreaks reported to the Public Health Services Rott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…All these findings suggested that COVID-19-related NPIs through reducing human-to-human contact and environmental exposure might prevent the transmission of fecal-oral-, vector-borne, and direct-contact transmitted NIDs. In contrast to previous studies [12] , [18] , [19] , [20] , which investigated the short-term effect of NPI during early pandemic, our findings indicated that the effect of continuing NPIs can persistent for two years…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…All these findings suggested that COVID-19-related NPIs through reducing human-to-human contact and environmental exposure might prevent the transmission of fecal-oral-, vector-borne, and direct-contact transmitted NIDs. In contrast to previous studies [12] , [18] , [19] , [20] , which investigated the short-term effect of NPI during early pandemic, our findings indicated that the effect of continuing NPIs can persistent for two years…”
Section: Discussioncontrasting
confidence: 99%
“…The decreasing fecal-oral-, vector-borne, and direct-contact transmitted NIDs during pandemic were consistent with previous studies in other countries [12] , [18] , [19] , [20] . In Netherland, gastrointestinal-related NIDs, such as norovirus disease, hepatitis A and shigellosis and travel-related NIDs, such as malaria, Zika, typhoid fever, cholera, yellow fever and paratyphus were reported 50% less often during the first wave of the COVID-19 epidemic than in the corresponding period in 2017–2019 [18] . In Japan, lower activity of several contact transmitted, and fecal-oral transmitted diseases was observed in 2020 than that in 2015-2019 [12] .…”
Section: Discussionsupporting
confidence: 92%
“…gloves, hand sanitiser, cleaning of surfaces and equipment, etc.) or even in reducing travel-related FBOs, as observed in the literature (Ray et al, 2021;van Deursen et al, 2022). The diversion of technical, financial and human resources towards activities relating to the COVID-19 pandemic may also have had an important role.…”
Section: Health Impact Causative Agents and Trendsmentioning
confidence: 93%
“…While Crane et al (2022) [ 119 ] expressed reservations as to whether decreased reporting (or ‘notification’) of almost all nationally notifiable infectious diseases (NIDs) in the United States reflected a true decrease in disease, an impairment of notification processes, or a combination of the two; other authors reported confidently of decreases in incidence of diseases transmitted by droplet or contact in Japan [ 120 ] and of respiratory and gastrointestinal infections in Germany [ 121 ] and the Netherlands [ 122 ]. Xiao et al (2021) [ 123 ] reported decreases in incidence of a broader range of NIDs, including insect-borne diseases such as typhus and dengue, as well as respiratory and gastrointestinal diseases.…”
Section: Review Resultsmentioning
confidence: 99%